Pasteurization For Water: Unit Testing And Potential For Commercial Application - Apriliawan, Hadi (Jurnal Inovasi Teknologi Terapan, 2024)
Waterborne diseases continue to pose a significant global health challenge. Traditional water treatment methods often fall short in ensuring complete microbial inactivation. This study investigates the efficacy of pasteurization as a potential solution for water disinfection. The research focuses on unit testing the pasteurization process to determine optimal temperature and exposure time for effective pH level. Water, being a fundamental component in numerous pasteurization processes, undergoes significant changes when subjected to heat. This study involves five steps to analyze pH changes in water during pasteurization. Starting at 50°C, a water sample is taken and its pH level measured. The temperature is then increased to 60°C, 70°C, 80°C, and 90°C, with pH measurements taken at each step. The recorded pH levels are compared to determine the effect of temperature on water pH, leading to a comprehensive conclusion based on the observed data. The result shows that increasing the temperature during pasteurization leads to an increase in the pH level of water. Consequently, for applications requiring a specific pH level, such as the ideal pH [1] a pasteurization  temperature of 90°C is recommended. The Environmental Protection Agency (EPA) of the united states recommends a pH level of 7 for daily consumption.